"I had always operated on the outside": A conversation with E. Roy Weintraub on the history of economics, science studies and academic morals - Yann Giraud (Duke University, Center for the History of Political Economy (CHOPE), 2019)
A transcription of a 2019 conversation with Duke historian E. Roy Weintraub on his intellectual development over the 1980s from mathematician to economist to historian. The conversation also explored Weintraub's early and continuing attempts to forge new ways to study the history of contemporary economics, and the role of science studies in providing a natural language for such explorations. The interview will be translated by Giraud and published in French in the journal "Zilsel: Science, technique, société".
Keywords: A11; A12; A14; B20; B40; B41; 330; E. Roy Weintraub; historiography; constructivism; science studies; Sidney Weintraub; academic ethics